Using expectancy-value theory to understand academic self-control. (December 2018) - Galla, Brian M.; Amemiya, Jamie; Wang, Ming-Te
Abstract: We applied expectancy-value theory to understand academic self-control. In three studies of middle and high school students ( N total = 2620), subjective values, but not expectancy beliefs, predicted motivation and behavior toward academic activities over alternative activities. Moreover, results showed that intrinsic value was a stronger incremental predictor of academic self-control compared to utility value. Study 1 used experience sampling and showed that momentary perceptions of intrinsic value were more strongly associated with motivational conflict during engagement in academic activities compared to perceptions of utility value. Study 2 used daily diaries and demonstrated that intrinsic value predicted greater self-control for homework over 14 days. Study 3 was a longitudinal study that showed the proposed framework generalized across math and science: Compared to utility value, intrinsic value of math and science were more strongly associated with academic self-control in each subject. Collectively, results suggest that enhancing enjoyment of academics may encourage greater self-control. Highlights: In three studies, we used expectancy-value theory to understand academic self-control. Intrinsic value and utility value, but not expectancy beliefs, predicted self-control. Intrinsic value emerged as a stronger and more reliable predictor of self-control. Results suggest that academic self-control is a type of value-based choice. Enhancing enjoyment of academic tasks may encourage greater self-control.